Resin composition and uses of the same

TW202633995AActive Publication Date: 2026-08-16TAIWAN UNION TECHNOLOGY CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
TW114104552
Authority / Receiving Office
TW · TW
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2026-08-16
Estimated Expiration
2045-02-06

AI Technical Summary

Technical Problem

Bismaleimide-based resin compositions for printed circuit boards face challenges in machinability and multi-layer hot-pressing thermal resistance, failing to meet the demands of high-frequency applications and lead-free manufacturing processes.

Method used

A resin composition combining bismaleimide resin, cyanate ester resin with a specific molecular weight, and benzoxazine compound, enhancing machinability and heat resistance without compromising thermal stability.

Benefits of technology

The composition improves machinability and multi-layer hot-pressing heat resistance, maintaining high glass transition temperature and thermal stability, suitable for high-frequency applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

and (C) a benzoxazine compound. A prepreg prepared from the resin composition, a metal-clad laminate prepared from the prepreg and a printed circuit board prepared from the metal-clad laminate are also provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a resin composition, and more specifically, to a resin composition comprising a bismaleimide resin, a cyanate resin having a specific number average molecular weight (Mn), and a benzoxazine compound. This invention also relates to a prepreg, a metal foil laminate, and a printed circuit board made from this resin composition. [Previous Technology]

[0002] As electronic products continue to move towards higher frequencies, higher speeds, smaller sizes, and higher circuit densities, the requirements for the dielectric properties of electronic materials are also increasing, demanding lower dielectric constants (Dk) and dielectric dissipation factors (Df). Furthermore, due to the requirements of lead-free manufacturing processes, the processing temperature of printed circuit boards (PCBs) has become higher, thus increasing the requirements for the heat resistance of the PCB dielectric layer materials.

[0003] In the prior art, bismaleimide resin compositions comprising bismaleimide resin and cyanate ester resin are often used as dielectric layer materials. However, although bismaleimide resin compositions have many advantages such as high glass transition temperature (Tg), high heat resistance, moisture resistance, low Dk and low Df, the machinability of the resulting laminates is poor and cannot meet current process requirements.

[0004] Therefore, there is still a need for an electronic material that combines a high upper limit on the number of boreholes, high Tg and multi-layer hot-pressing thermal resistance to be suitable for various high-frequency applications. [Summary of the Invention]

[0005] In view of the above technical problems, the present invention provides a resin composition comprising a bismaleimide resin, a cyanate resin having a specific number of average molecular weights, and a benzoxazine compound. By combining a cyanate resin having a specific number of average molecular weights, a bismaleimide resin, and a benzoxazine compound, the present invention can significantly improve the machinability (based on the maximum number of holes tested) and multilayer hot pressing heat resistance of electronic materials made from the resin composition without reducing the Tg and heat resistance.

[0006] Therefore, one object of the present invention is to provide a resin composition comprising: (A) a bismaleimide resin; (B) a cyanate resin having an amount average molecular weight of 1,000 to 3,000; and (C) a benzoxazine compound.

[0007] In one embodiment of the present invention, the bismaleimide resin (A) has a structure represented by the following formula (I): [Formula (I)], in which R4 is selected from the group consisting of methylene (-CH2-), 4,4'-diphenylmethane (), m-phenylene (), bisphenol A diphenyl etheryl (), 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane (), 4-methyl-1,3-phenylene (), (2,2,4-trimethyl)-1,6-hexyl (), and, where k is an integer from 0 to 5.

[0008] In one embodiment of the present invention, the bismaleimide resin (A) is selected from the group consisting of: 1,2-bismaleiminoethane, 1,6-bismaleiminohexane, 1,3-bismaleiminobenzene, 1,4-bismaleiminobenzene, 2,4-bismaleiminotoluene, 4,4'-bismaleiminodiphenylmethane, 4,4'-bismaleiminodiphenyl ether, 3,3'-bismaleiminodiphenyl ether, 4,4 ... -Dimaleiminodiphenyl sulfonium, 4,4'-Dimaleiminodicyclohexylmethane, 3,5-bis(4-maleiminophenyl)pyridine, 2,6-bismaleiminopyridine, 1,3-bis(maleiminomethyl)cyclohexane, 1,3-bis(maleiminomethyl)benzene, 1,1-bis(4-maleiminophenyl)cyclohexane, 1,3-bis(dichloromaleimino)benzene, 4,4' -4,4'-biscitraconimidodiphenylmethane, 2,2-bis(4-maleiminophenyl)propane, 1-phenyl-1,1-bis(4-maleiminophenyl)ethane, α,α-bis(4-maleiminophenyl)toluene, 3,5-bismaleimino-1,2,4-triazole, N,N'-extrin Ethyl bismaleimide, N,N'-hexamethylene bismaleimide, N,N'-m-extrinylphenyl bismaleimide, N,N'-p-extrinylphenyl bismaleimide, N,N'-α,α'-4,4'-dimethylenecyclohexane bismaleimide, N,N'-m-xylene bismaleimide, N,N'-4,4'-diphenylcyclohexane bismaleimide, and combinations thereof, wherein y is an integer from 1 to 4.

[0009] In one embodiment of the present invention, the cyanate resin (B) is selected from the group consisting of: 2,2-bis(4-cyanoxyphenyl)propane, 4,4'-ethylidene bis(phenyl) cyanate (4,4'-ethylidene) Bisphenylenecyanate, 4,4'-dicyanoxybiphenyl, bis(4-cyanoxy-3,5-dimethylbenzene)methane, bis(4-cyanoxyphenyl)sulfide, bis(4-cyanoxyphenyl) ether, prepolymers of bisphenol A dicyanate, 1,1-bis(4-cyanoxyphenyl)ethane, 1,1-bis(4-cyanoxyphenyl)methane, 1,3-bis(4-cyanoxyphenyl-1-(methylethylidene))benzene, bis(4-cyanoxyphenyl) ether, bis(4-cyanoxyphenyl)-2,2-butane, 1,3-bis[2-(4-cyanoxyphenyl)propyl]benzene, bis(4-cyanoxyphenyl)ethane, cyano-modified phenolic aldehydes, cyano-modified phenolic dicyclopentadiene adducts, and combinations thereof.

[0010] In one embodiment of the present invention, the resin composition further comprises a curing accelerator selected from the group consisting of imidazole compounds, pyridine compounds, and combinations thereof.

[0011] In one embodiment of the present invention, the resin composition further comprises a curing agent selected from the group consisting of styrene, α-methylstyrene, ethylstyrene, propylstyrene, butylstyrene, triallyl isocyanurate (TAIC), triallyl cyanurate (TAC), 1,3-divinylbenzene, 1,4-divinylbenzene, 1,2-bis(p-vinylphenyl)ethane, 1,2-bis(m-vinylphenyl)ethane, 1-(p-vinylphenyl)-2-(m-vinylphenyl)ethane, and combinations thereof.

[0012] In one embodiment of the present invention, the resin composition further comprises fillers selected from the group consisting of: silica (including spherical silica, molten silica, non-molten silica, porous silica, hollow silica, and nano silica), alumina, magnesium oxide, magnesium hydroxide, calcium carbonate, talc, clay, aluminum nitride, boron nitride, aluminum hydroxide, aluminum carbide silica, silica, sodium carbonate, titanium dioxide, zinc oxide, zirconium oxide, quartz, diamond, diamond-like material, graphite, calcined kaolin, bailing, mica, hydrotalcite, hollow silica, polytetrafluoroethylene (PTFE) powder, glass beads, ceramic whiskers, carbon nanotubes, nano-sized inorganic powders, and combinations thereof.

[0013] Another object of the present invention is to provide a semi-cured sheet, which is prepared by impregnating or coating a substrate with the resin composition described above and drying the impregnated or coated substrate.

[0014] Another object of the present invention is to provide a metal foil laminate, which is made by laminating a prepreg as described above with a metal foil, or by directly coating a resin composition as described above onto a metal foil and drying the metal foil.

[0015] Another object of the present invention is to provide a printed circuit board made of the metal foil laminate as described above.

[0016] In order to make the above-mentioned objectives, technical features and advantages of the present invention more apparent and understandable, the following is a detailed description of some specific embodiments.

Implementation Method

[0017] The following will specifically describe some specific embodiments of the present invention; however, the present invention may be practiced in many different forms and the scope of protection of the present invention should not be limited to the specific embodiments described.

[0018] Unless otherwise stated, the terms “a”, “the” and similar terms used in this specification and the claims shall be understood to include both singular and plural forms.

[0019] Unless otherwise stated, when describing the components contained in solutions, mixtures, compositions or adhesives in this specification and the claims, the weight of the solvent is not included.

[0020] In this article, the unit of "number average molecular weight (Mn)" is Dalton.

[0021] The resin composition of the present invention combines a bismaleimide resin, a cyanate ester resin having a specific number of average molecular weights, and a benzoxazine compound. Through the synergistic effect of these components, the machinability and heat resistance of the resulting electronic material can be significantly improved without compromising its high Tg and heat resistance. The following provides a detailed description of the resin composition of the present invention and its related applications.

[0022] 1. Resin composition

[0023] The resin composition of the present invention comprises (A) bismaleimide resin, (B) cyanate ester resin with a number average molecular weight of 1000 to 3000, and (C) benzoxazine compound, as well as other optional components as needed. Detailed descriptions of each component are as follows.

[0024] 1.1. Bismaleimide resin (A)

[0025] In this document, bismaleimide resin refers to a resin having at least two maleimide functional groups, wherein the maleimide functional group refers to an unsaturated maleimide functional group having a reactive double bond. Components having maleimide functional groups can react with other components having unsaturated groups due to the presence of reactive double bonds. In one embodiment of the present invention, the bismaleimide resin (A) has a structure as shown in the following formula (I): [Formula (I)], in which R4 is selected from the group consisting of methylene (-CH2-), 4,4'-diphenylmethane (), m-phenylene (), bisphenol A diphenyl etheryl (), 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane (), 4-methyl-1,3-phenylene (), (2,2,4-trimethyl)-1,6-hexyl (), and, where k is an integer from 0 to 5.

[0026] Specific examples of bismaleimide resins (A) that can be used in the resin compositions of the present invention include, but are not limited to, 1,2-bismaleiminoethane, 1,6-bismaleiminohexane, 1,3-bismaleiminobenzene, 1,4-bismaleiminobenzene, 2,4-bismaleiminotoluene, 4,4'-bismaleiminodiphenylmethane, 4,4'-bismaleiminodiphenyl ether, 3,3'- Bismaleiminodiphenyl sulfonate, 4,4'-bismaleiminodiphenyl sulfonate, 4,4'-bismaleiminodicyclohexylmethane, 3,5-bis(4-maleiminophenyl)pyridine, 2,6-bismaleiminopyridine, 1,3-bis(maleiminomethyl)cyclohexane, 1,3-bis(maleiminomethyl)benzene, 1,1-bis(4-maleiminophenyl)cyclohexane, 1,3-bis(dichlorophenyl)cyclohexane (Hydroxyimino)benzene, 4,4'-biscitraconimidodiphenylmethane, 2,2-bis(4-maleiminophenyl)propane, 1-phenyl-1,1-bis(4-maleiminophenyl)ethane, α,α-bis(4-maleiminophenyl)toluene, 3,5-bismaleimino-1,2,4-triphenyliminophenyl The resins are azoles, N,N'-epenylethyl bismaleimide, N,N'-hexamethylene bismaleimide, N,N'-m-epenylphenyl bismaleimide, N,N'-p-epenylphenyl bismaleimide, N,N'-α,α'-4,4'-dimethylenecyclohexane bismaleimide, N,N'-m-xylene bismaleimide, N,N'-4,4'-diphenylcyclohexane bismaleimide, and y, wherein y is an integer from 1 to 4. The aforementioned bismaleimide resins can be used alone or in combination.

[0027] Commercially available bismaleimide resins include, but are not limited to, the following products: products with model numbers BMI-70 and BMI-80 purchased from KI Chemical, products with model number MIR-3000-70MT purchased from Nippon Kayaku, and products with model numbers BMI-1000, BMI-2000, BMI-2300, BMI-4000, BMI-5000, BMI-5100, and BMI-7000 purchased from Daiwa Kasei Industry (Wakayama, Japan).

[0028] In the resin composition of the present invention, based on 100 parts by weight of the total weight of the solvent-free bismaleimide resin (A), cyanate ester resin (B), and benzoxazine compound (C), the amount of bismaleimide resin (A) can be from 20 parts by weight to 80 parts by weight, for example 20 parts by weight, 21 parts by weight, 22 parts by weight, 23 parts by weight, 24 parts by weight, 25 parts by weight, 26 parts by weight, 27 parts by weight, 28 parts by weight, 29 parts by weight, 30 parts by weight, 31 parts by weight, 32 parts by weight, 33 parts by weight, 34 parts by weight, 35 parts by weight, 36 parts by weight, 37 parts by weight, 38 parts by weight, 39 parts by weight, 40 parts by weight, 41 parts by weight, 42 parts by weight, 43 parts by weight. The quantities are 44 parts by weight, 45 parts by weight, 46 parts by weight, 47 parts by weight, 48 parts by weight, 49 parts by weight, 50 parts by weight, 51 parts by weight, 52 parts by weight, 53 parts by weight, 54 parts by weight, 55 parts by weight, 56 parts by weight, 57 parts by weight, 58 parts by weight, 59 parts by weight, 60 parts by weight, 61 parts by weight, 62 parts by weight, 63 parts by weight, 64 parts by weight, 65 parts by weight, 66 parts by weight, 67 parts by weight, 68 parts by weight, 69 parts by weight, 70 parts by weight, 71 parts by weight, 72 parts by weight, 73 parts by weight, 74 parts by weight, 75 parts by weight, 76 parts by weight, 77 parts by weight, 78 parts by weight, 79 parts by weight, 80 parts by weight, or within the range of any two of the above values. However, the present invention is not limited thereto, and those skilled in the art can adjust the dosage according to actual needs.

[0029] In the resin composition of the present invention, based on 100% by weight of the total weight of the solvent-free resin composition, the content of bismaleimide resin (A) is preferably 10% to 60% by weight, for example 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% by weight. 31% by weight, 32% by weight, 33% by weight, 34% by weight, 35% by weight, 36% by weight, 37% by weight, 38% by weight, 39% by weight, 40% by weight, 41% by weight, 42% by weight, 43% by weight, 44% by weight, 45% by weight, 46% by weight, 47% by weight, 48% by weight, 49% by weight, 50% by weight, 51% by weight, 52% by weight, 53% by weight, 54% by weight, 55% by weight, 56% by weight, 57% by weight, 58% by weight, 59% by weight, or 60% by weight, or within the range consisting of any two of the above values.

[0030] 1.2. Cyanate ester resin (B)

[0031] In this document, cyanate ester resin (B) refers to a resin having a -OCN functional group. In one embodiment of the present invention, the cyanate ester resin is a chemical substance derived from a bisphenol derivative or a phenolic derivative, wherein at least one hydroxyl group (-OH) of the bisphenol derivative or phenolic derivative is substituted with a cyano group to form a -OCN functional group. Because the cyanate ester resin has a -OCN functional group, it can form a trimer through a cross-linking reaction, or form a network structure by cross-linking with other components having unsaturated functional groups.

[0032] Specific examples of cyanate resins (B) include, but are not limited to, 2,2-bis(4-cyanoxyphenyl)propane, 4,4'-ethylene bis(phenyl) cyanate, 4,4'-dicyanoxybiphenyl, bis(4-cyanoxy-3,5-dimethylphenyl)methane, bis(4-cyanoxyphenyl) sulfide, bis(4-cyanoxyphenyl) ether, prepolymers of bisphenol A dicyanate, 1,1-bis(4-cyanoxyphenyl)ethane, 1,1-bis(4-cyanoxyphenyl)methane, 1,3-bis(4-cyanoxyphenyl-1-(methylethylene))benzene, bis(4-cyanoxyphenyl) ether, bis(4-cyanoxyphenyl)-2,2-butane, 1,3-bis[2-(4-cyanoxyphenyl)propyl]benzene, bis(4-cyanoxyphenyl)ethane, and cyano-oxidized phenolic resins and cyano-oxidized phenolic dicyclopentadiene adducts. The aforementioned cyanate resins can be used individually or in combination.

[0033] According to the present invention, the number average molecular weight (Mn) of the cyanate ester resin (B) is 1,000 to 3,000, having a number average molecular weight within a specific range. For example, the number average molecular weight of the cyanate ester resin (B) may be 1000, 1050, 1100, 1150, 1200, 1250, 1300, 1350, 1400, 1450, 1500, 1550, 1600, 1650, 1700, 1750, 1800, 1850, 1900, 1950, 2000, 2050, 2100, 2150, 2200, 2250, 2300, 2350, 2400, 2450, 2500, 2550, 2600, 2650, 2700, 2750, 2800, 2850, 2900, 2950, ​​or 3000, or fall within a range consisting of any two of the above values. By controlling the number-average molecular weight of the cyanate ester resin (B) within the specified range, the resin composition of the present invention can significantly improve the machinability and heat resistance of the electronic materials without compromising their heat resistance (Tg) and thermal properties. If the number-average molecular weight of the cyanate ester resin (B) is higher or lower than the specified range, the machinability of the electronic materials will be poor.

[0034] Commercially available cyanate ester resins include, but are not limited to, the TA1000S product (Mn 2500 to 3000) purchased from Yangzhou Tianqi New Materials. Alternatively, cyanate ester resin (B) can also be prepared as follows: First, the cyanate ester monomer is dissolved in an organic solvent to obtain a homogeneous solution. Then, the homogeneous solution is placed under a nitrogen atmosphere and stirred at 70°C to 130°C for 3 to 7 hours to carry out a polymerization reaction. Afterwards, the solvent is removed using a rotary thiocyanate separator to obtain a crude product. The crude product is then washed several times with methanol, and the solvent is removed again using a rotary thiocyanate separator to obtain the cyanate ester resin. Examples of the organic solvents include, but are not limited to, benzene, toluene, xylene, hexane, cyclohexane, heptane, decane, γ-butyrolactone, methyl ethyl ketone, cyclohexanone, butanone, and acetone. The aforementioned organic solvents can be used alone or in combination. In the examples attached below, toluene is used.

[0035] In the resin composition of the present invention, based on 100 parts by weight of the total weight of the solvent-free bismaleimide resin (A), cyanate ester resin (B), and benzoxazine compound (C), the amount of cyanate ester resin (B) can be from 15 parts by weight to 50 parts by weight, for example 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, 21 parts by weight, 22 parts by weight, 23 parts by weight, 24 parts by weight, 25 parts by weight, 26 parts by weight, etc. The quantities are 27 parts by weight, 28 parts by weight, 29 parts by weight, 30 parts by weight, 31 parts by weight, 32 parts by weight, 33 parts by weight, 34 parts by weight, 35 parts by weight, 36 parts by weight, 37 parts by weight, 38 parts by weight, 39 parts by weight, 40 parts by weight, 41 parts by weight, 42 parts by weight, 43 parts by weight, 44 parts by weight, 45 parts by weight, 46 parts by weight, 47 parts by weight, 48 parts by weight, 49 parts by weight, or 50 parts by weight, or a range consisting of any two of the above values. However, the present invention is not limited thereto, and those skilled in the art can adjust the dosage according to actual needs.

[0036] In the resin composition of the present invention, the content of cyanate ester resin (B) is preferably 7% to 35% by weight, based on 100% by weight of the total weight of the solvent-free resin composition, for example, 7% by weight, 8% by weight, 9% by weight, 10% by weight, 11% by weight, 12% by weight, 13% by weight, 14% by weight, 15% by weight, 16% by weight, 17% by weight, 18% by weight, 19% by weight, 20% by weight, 21% by weight, 22% by weight, 23% by weight, 24% by weight, 25% by weight, 26% by weight, 27% by weight, 28% by weight, 29% by weight, 30% by weight, 31% by weight, 32% by weight, 33% by weight, 34% by weight, or 35% by weight, or within the range of any two of the above values.

[0037] 1.3. Benzoxazine compounds (C)

[0038] In this document, benzoxazine compound refers to a compound having at least one benzoxazine structure, where the benzoxazine structure refers to a bicyclic heterocyclic structure formed by the fusion of a benzene ring and an oxazine ring. In one embodiment of the present invention, benzoxazine compound (C) can be prepared by reacting a phenolic hydroxyl compound, a monoamine compound, and formaldehyde according to the following reaction formula (z). [Reaction formula (z)]

[0039] In reaction formula (z), R1 is an alkyl, cycloalkyl, phenyl, or a phenyl substituted with an alkyl or alkoxy group. Examples of alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, secondary butyl, tertiary butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, n-heptyl, isoheptyl, n-octyl, isooctyl, n-nonyl, isononyl, n-decyl, and isodel. Examples of cycloalkyl groups include, but are not limited to, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, and cyclodecyl. Examples of alkoxy groups include, but are not limited to, methoxy, ethoxy, propoxy, butoxy, pentoxy, and hexoxy. Phenolic hydroxyl compounds may be polyfunctional phenols, biphenols, bisphenols, triphenols, and phenolic resins. Examples of polyfunctional phenols include, but are not limited to, catechol, resorcinol, and hydroquinone. Examples of bisphenol compounds include, but are not limited to, bisphenol A, bisphenol F, and bisphenol S. Examples of phenolic resins include, but are not limited to, phenolic varnish resins and melamine-phenolic resins. Examples of monoamine compounds include, but are not limited to, methylamine, aniline, and aniline substituted with alkyl or alkoxy groups.

[0040] In one embodiment of the present invention, the benzoxazine compound (C) may be a benzoxazine prepolymer that has undergone a ring-opening reaction. The preparation method of the benzoxazine prepolymer is not the focus of the present invention and will not be described in detail here. For specific preparation methods, please refer to, for example, US 2012 / 0097437 A1, the entire text of which is incorporated herein by reference. The benzoxazine compound (C) may contain one or more benzoxazine compounds. Commercially available benzoxazine compounds include, but are not limited to, the product LZ 8280 purchased from Huntsman, the product PF-3500 purchased from Chang Chun Chemical, and the products JBZ-100N, JBZ-BF100N, and JBZ-BA100N purchased from JFE Chemicals.

[0041] In the resin composition of the present invention, based on 100 parts by weight of the total weight of the solvent-free bismaleimide resin (A), cyanate ester resin (B), and benzoxazine compound (C), the amount of benzoxazine compound (C) can be from 1 part by weight to 15 parts by weight, for example, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, or 15 parts by weight, or within the range of any two of the above values. However, the present invention is not limited thereto, and those skilled in the art can adjust the amount according to actual needs.

[0042] In the resin composition of the present invention, the content of benzoxazine compound (C) is preferably 1% to 15% by weight, based on 100% by weight of the total weight of the solvent-free resin composition, for example, 1% by weight, 2% by weight, 3% by weight, 4% by weight, 5% by weight, 6% by weight, 7% by weight, 8% by weight, 9% by weight, 10% by weight, 11% by weight, 12% by weight, 13% by weight, 14% by weight, or 15% by weight, or within the range of any two of the above values.

[0043] 1.4. Other ingredients to be selected as needed

[0044] The resin composition of the present invention may further include other optional components as needed to adaptively improve the processability of the resin composition during the manufacturing process or to improve the physicochemical properties of the electronic materials made from the resin composition. These optional components include, but are not limited to, curing accelerators, curing agents, fillers, dispersants, elastomers, toughening agents, viscosity modifiers, flame retardants, coupling agents, and other known additives in the art, such as epoxy resins, thermosetting polyphenylene ether resins, and thermosetting phenolic resins. The use of such optional components is as needed by those skilled in the art upon viewing the disclosure of this specification. The following description only exemplifies curing accelerators, curing agents, and fillers.

[0045] [Hardening Accelerator]

[0046] The curing accelerator can promote the curing reaction and lower the curing reaction temperature of the resin composition. There are no particular limitations on the type of curing accelerator, as long as it is suitable for promoting the curing reaction of the resin composition of the present invention and lowering the curing reaction temperature. In one embodiment of the present invention, the curing accelerator is an imidazole compound, a pyridine compound, or a combination thereof. Examples of imidazole compounds include, but are not limited to, 2-methyl-imidazole (2MI), 2-ethyl-4-methyl-imidazole (2E4MZ), and 2-phenyl-imidazole (2PI). The aforementioned imidazole compounds can be used alone or in combination. Examples of pyridine compounds include, but are not limited to, 2,3-diaminopyridine, 2,5-diaminopyridine, 2,6-diaminopyridine, 4-dimethylaminopyridine, 2-amino-3-methylpyridine, 2-amino-4-methylpyridine, and 2-amino-3-nitropyridine. The aforementioned pyridine compounds can be used alone or in combination. In the examples attached below, 2PI is used.

[0047] The content of the curing accelerator can be adjusted according to actual needs and is not particularly limited. Generally speaking, based on 100 parts by weight of the total weight of solvent-free bismaleimide resin (A), cyanate ester resin (B), and benzoxazine compound (C), the amount of curing accelerator can be from 0 parts by weight to 0.5 parts by weight, for example, 0.01 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.15 parts by weight, 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.35 parts by weight, 0.4 parts by weight, 0.45 parts by weight, or 0.5 parts by weight, or within the range of any two of the above values. However, the present invention is not limited thereto, and those skilled in the art can adjust the amount according to actual needs.

[0048] [Hardening agent]

[0049] The curing agent has unsaturated functional groups and can undergo cross-linking reactions with other components having unsaturated functional groups (such as bismaleimide resin or cyanate ester resin) to form a three-dimensional network structure, thereby increasing the degree of cross-linking. The unsaturated functional group refers to a group that can undergo addition polymerization reactions with other components having unsaturated functional groups by light or heat. Examples of unsaturated functional groups include, but are not limited to, vinyl, vinyl benzyl, allyl, acrylate, and methacrylic.

[0050] There are no particular limitations on the type of hardener, including but not limited to monovinyl compounds, polyfunctional allyl compounds, polyfunctional acrylates, polyfunctional acrylamides, and polyfunctional styrene compounds. The aforementioned hardeners can be used alone or in combination. In one embodiment of the present invention, the hardener is selected from the group consisting of styrene, α-methylstyrene, ethylstyrene, propylstyrene, butylstyrene, TAIC, TAC, 1,3-divinylbenzene, 1,4-divinylbenzene, 1,2-bis(p-vinylphenyl)ethane, 1,2-bis(m-vinylphenyl)ethane, 1-(p-vinylphenyl)-2-(m-vinylphenyl)ethane, and combinations thereof.

[0051] The content of the hardener can be adjusted according to actual needs and there are no special restrictions. Generally speaking, based on 100 parts by weight of the total weight of solvent-free bismaleimide resin (A), cyanate ester resin (B), and benzoxazine compound (C), the content of the hardener can be from 0 parts by weight to 10 parts by weight, for example, 0.1 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, or 10 parts by weight, or within the range of any two of the above values.

[0052] [Packaging]

[0053] The resin composition of the present invention may further include fillers to improve the mechanical strength, thermal conductivity and dimensional stability of the resulting electronic materials. Examples of suitable fillers include, but are not limited to, fillers selected from the group consisting of: silica (including spherical silica, molten silica, nonmolten silica, porous silica, hollow silica and nano silica), alumina, magnesium oxide, magnesium hydroxide, calcium carbonate, talc, clay, aluminum nitride, boron nitride, aluminum hydroxide, aluminum carbide silica, silica carbide, sodium carbonate, titanium dioxide, zinc oxide, zirconium oxide, quartz, diamond, diamond-like materials, graphite, calcined kaolin, baiji, mica, hydrotalcite, hollow silica, PTFE powder, glass beads, ceramic whiskers, carbon nanotubes, nano-scale inorganic powders and combinations thereof.

[0054] The filler content can be adjusted according to actual needs and there are no special restrictions. Generally speaking, based on 100 parts by weight of the total weight of solvent-free bismaleimide resin (A), cyanate ester resin (B), and benzoxazine compound (C), the filler content can be from 50 parts by weight to 300 parts by weight, for example, 50 parts by weight, 55 parts by weight, 60 parts by weight, 65 parts by weight, 70 parts by weight, 75 parts by weight, 80 parts by weight, 85 parts by weight, 90 parts by weight, 95 parts by weight, 100 parts by weight, 105 parts by weight, 110 parts by weight, 115 parts by weight, 120 parts by weight, 125 parts by weight, 130 parts by weight, 135 parts by weight, 140 parts by weight, 145 parts by weight, 150 parts by weight, and 155 parts by weight. 160 parts by weight, 165 parts by weight, 170 parts by weight, 175 parts by weight, 180 parts by weight, 185 parts by weight, 190 parts by weight, 195 parts by weight, 200 parts by weight, 205 parts by weight, 210 parts by weight, 215 parts by weight, 220 parts by weight, 225 parts by weight, 230 parts by weight, 235 parts by weight, 240 parts by weight, 245 parts by weight, 250 parts by weight, 255 parts by weight, 260 parts by weight, 265 parts by weight, 270 parts by weight, 275 parts by weight, 280 parts by weight, 285 parts by weight, 290 parts by weight, 295 parts by weight, or 300 parts by weight, or a range consisting of any two of the above values.

[0055] 1.5. Preparation of Resin Composition

[0056] Regarding the preparation of the resin composition of the present invention, the components of the resin composition, including bismaleimide resin (A), cyanate ester resin with a molecular weight of 1000 to 3000 (B), benzoxazine compound (C), and other optional components, can be uniformly mixed and dissolved or dispersed in a solvent using a stirrer to form a varnish-like form for subsequent processing. The solvent can be any inert solvent capable of dissolving or dispersing the components of the resin composition but not reacting with them. For example, solvents that can be used to dissolve or disperse the components of the resin composition include, but are not limited to: toluene, γ-butyrolactone, methyl ethyl ketone, cyclohexanone, butanone, acetone, xylene, methyl isobutyl ketone, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methylpyrolidone (NMP). Each solvent can be used alone or in combination. There are no particular restrictions on the amount of solvent used; in principle, it is sufficient to ensure that all components of the resin composition are uniformly dissolved or dispersed therein. In the examples attached below, methyl ethyl ketone (MEK) was used as the solvent.

[0057] 2. Application of resin compositions

[0058] The resin composition of the present invention can be applied to the preparation of prepregs, metal foil laminates, and printed circuit boards. Therefore, the present invention also provides a prepreg, a metal foil laminate, and a printed circuit board prepared from the above-mentioned resin composition. Detailed descriptions of each application are as follows.

[0059] 2.1. Prepreg

[0060] The present invention also provides a semi-cured sheet made from the above-described resin composition, which is obtained by impregnating or coating a substrate with the resin composition described above and drying the impregnated or coated substrate. Methods for impregnating or coating the resin composition include, but are not limited to, impregnation, roller coating, die coating, rod coating, gravure coating, spin coating, slot coating, and spraying. The impregnated or coated substrate can be dried at a temperature of 100°C to 200°C for 1 to 20 minutes to obtain a semi-cured sheet in a semi-cured state (B-stage). In the examples attached below, drying is performed at 175°C for 2 to 15 minutes.

[0061] The substrate may be any reinforcing material known in the art. Generally, reinforcing materials include, but are not limited to, spherical glass and fibers selected from the group consisting of: glass fibers, inorganic fibers other than glass fibers, organic fibers, and combinations thereof. Examples of glass fibers include, but are not limited to, E-glass, NE-glass, S-glass, L-glass, D-glass, T-glass, Q-glass, and UN-glass. Examples of inorganic fibers other than glass fibers include, but are not limited to, quartz fibers, paper fibers, and carbon fibers. Examples of organic fibers include, but are not limited to, polyimide fibers, polyimide fibers (e.g., Kevlar fibers), polytetrafluoroethylene fibers, ultra-high molecular weight polyethylene (UHMWPE) fibers, high-modulus polypropylene (HMPP) fibers, and liquid crystal polymer (LCP) fibers. The forms of reinforcing materials include, but are not limited to, woven fabrics, nonwoven fabrics, rovings, woven felt, and surface felt.

[0062] 2.2. Metal foil laminate

[0063] The present invention also provides a metal foil laminate made from the above-mentioned prepreg, which is obtained by laminating the prepreg and metal foil as described above, wherein the prepreg serves as a dielectric layer and the metal foil serves as a conductive layer. Alternatively, the metal foil laminate of the present invention can be obtained by directly coating the resin composition described above onto a metal foil and drying the metal foil, wherein the dried resin composition forms a dielectric layer and the metal foil serves as a conductive layer.

[0064] In one embodiment of the present invention, the metal foil laminate of the present invention can be prepared by: stacking multiple layers of prepreg, then stacking a metal foil (such as copper foil) on at least one outer surface of the dielectric layer formed by the stacked prepreg to provide a laminate comprising a dielectric layer and a metal layer, and performing a hot pressing operation on the laminate to obtain the metal foil laminate. The hot pressing operation conditions can be as follows: hot pressing for 60 to 240 minutes at a temperature of 180°C to 240°C and a pressure of 10 kg / cm² to 25 kg / cm² (initial pressure of 5 kg / cm² to 12 kg / cm²).

[0065] 2.3. Printed Circuit Board

[0066] The metal foil laminate of the present invention can be further patterned to form a printed circuit board. Therefore, the present invention also provides a printed circuit board which is made by further patterning the metal foil of the metal foil laminate of the present invention, wherein the method of patterning the metal foil is not particularly limited, and examples include but are not limited to photolithography.

[0067] 3. Example

[0068] 3.1. Measurement Method Description

[0069] The present invention will be further illustrated by the following specific embodiments, wherein the measuring instruments and methods used are as follows:

[0070] [Measurement of Number Average Molecular Weight]

[0071] The cyanate ester resin was dissolved or diluted with tetrahydrofuran to prepare a test solution with a concentration of 0.5% by mass. Then, the number average molecular weight (Mn) of the cyanate ester resin was measured using gel permeation chromatography (GPC) with a differential refractometer (model: HLC-8320GPC, purchased from Tosoh Corporation). The measurement conditions were as follows: the mobile phase was tetrahydrofuran, the flow rate was 1 mL / min, the column temperature was 30°C, and the columns were, in sequence, TSK Guardcolumn SuperHZ-L, TSK gel SuperHZM-N, TSK gel SuperHZM-M, and TSK gel SuperH-RC, all purchased from Tosoh Corporation, with monodisperse polystyrene as the molecular weight standard.

[0072] [Drilling Hole Count Limit Test]

[0073] Test samples were prepared as follows. First, glass fiber cloth (model: 1078, thickness: 0.05 mm) was impregnated in the resin composition using a roller coater, and the thickness of the glass fiber cloth was controlled to an appropriate level. Next, the impregnated glass fiber was placed in a dryer at 175°C and dried for 2 to 15 minutes to obtain a prepreg in a semi-cured state (stage B) (the resin content of the prepreg was approximately 52%), with a length of 33 cm and a width of 21.5 cm. Next, ten prepregs were laminated, with every two prepregs pressed together to form a layer, resulting in a five-layer laminate. Then, a 1 / 3 ounce copper foil was laminated to the outermost layer on each side of the laminate, and then it was placed in a hot press for high-temperature hot pressing curing. The hot-pressing conditions were as follows: the temperature was increased to 200°C to 220°C at a rate of 2.0°C / min to 3.0°C / min, and then hot-pressed at 200°C to 220°C for 180 minutes at a total pressure of 15 kg / cm² (initial pressure of 8 kg / cm²). The test sample was thus prepared.

[0074] The maximum number of holes drilled was tested as follows. First, a new drill bit (model MCW 0.105X1.9 Z935MWU, purchased from UNION TOOL) with a cutting edge length of 3.5 mm and a drill bit diameter of 0.1 mm was selected and mounted on a drilling machine (model super D6CMS, purchased from Suzhou Vega Technology). Next, the test sample was drilled at 195 krpm on the drilling machine. After drilling 1000 holes, the drill bit was removed, and the wear rate of the drill bit's cutting edge was observed using a microscope. The number of holes drilled when the drill bit's cutting edge wear rate was greater than 20% was recorded. The wear rate was obtained by observing the wear area of ​​the drill bit's cutting edge using a scanning electron microscope and calculating the ratio of the worn area to the total area of ​​the drill bit's cutting edge using a program. A higher number of holes indicates better drilling machinability.

[0075] [Measurement of glass transition temperature (Tg)]

[0076] The metal foil laminate used for evaluation was etched to remove the metal foil on both sides, resulting in an unclad laminate. Next, the glass transition temperature (Tg) of the unclad laminate was measured using a dynamic mechanical analysis (DMA, model: Q800, purchased from TA Instruments). The measurement conditions were as follows: a bending module was used at a frequency of 10 Hz, a heating rate of 5°C / min, and dynamic viscoelasticity was measured during the temperature rise from room temperature to 280°C. Tg is the temperature at which tanδ reaches its maximum value in the obtained viscoelastic curve.

[0077] [Heat resistance of multilayer hot pressing]

[0078] Test samples were prepared as follows. First, glass fiber cloth (model: 1078, thickness: 0.05 mm) was impregnated in a resin composition using a roller coater, and the thickness of the glass fiber cloth was controlled to an appropriate level. Next, the impregnated glass fiber was placed in a dryer at 175°C and dried for 2 to 15 minutes to obtain a prepreg in a semi-cured state (stage B) (the resin content of the prepreg was approximately 52%), with a length of 6.5 mm and a width of 6.5 mm. Next, six prepregs were laminated to obtain a stack. Then, a 1 / 3 ounce copper foil was laminated to the outermost layer on each side of the stack to obtain the test sample.

[0079] The multilayer hot-pressing heat resistance test was conducted as follows: The test sample was placed in a hot press and subjected to multiple high-temperature hot-pressing steps. The conditions for the high-temperature hot-pressing step were: heating to 190°C to 200°C at a heating rate of 3.0°C / min, and hot-pressing at 190°C to 200°C for 80 to 100 minutes at a total pressure of 15 kg / cm² to 30 kg / cm² (initial pressure 8 kg / cm²). After each high-temperature hot-pressing step, the surface of the test sample was observed for any protrusions forming a burst. If any were found, hot pressing was stopped, and the number of high-temperature hot-pressing steps was recorded. If none were found, the next high-temperature hot-pressing step was performed. The more times the high-temperature hot-pressing was performed, the better the multilayer hot-pressing heat resistance of the metal foil laminate.

[0080] 3.2. Raw Material Information List

[0081] Table 1: List of Raw Material Information model illustrate BMI-2300 Bismaleimide resin, purchased from Yamato Chemical Industry. BMI-70 Bismaleimide resin, purchased from Yamato Chemical Industry. MIR-3000-70MT Bismaleimide resin, purchased from Nippon Kayaku. JBZ-OP100N Benzoxazine compounds, purchased from Jefu Chemicals JBZ-BF100N Benzoxazine compounds, purchased from Jefu Chemicals JBZ-BA100N Benzoxazine compounds, purchased from Jefu Chemicals TA1000S Cyanate ester resin (Mn 2500 to 3000) was purchased from Yangzhou Tianqi New Materials. C01PS Cyanate ester resin (Mn 4000 to 40000) was purchased from Yangzhou Tianqi New Materials. CE01MO Cyanate ester resin (Mn 278) was purchased from Yangzhou Tianqi New Materials. C03CS Cyanate ester resin (Mn 350 to 400) was purchased from Yangzhou Tianqi New Materials. C05CS Cyanate ester resin (Mn 350 to 450) was purchased from Yangzhou Tianqi New Materials. C06MO Cyanate ester resin (Mn 306) was purchased from Yangzhou Tianqi New Materials. C09MO Cyanate ester resin (Mn 264) was purchased from Yangzhou Tianqi New Materials. CE07MO Cyanate ester resin (Mn 396) was purchased from Yangzhou Tianqi New Materials. SPB-100 Flame retardant, purchased from Otsuka Chemical. XZ92741 Flame retardant, purchased from BLUE CUBE (Blue Cube, USA). 2PI Hardening accelerator, purchased from Shikoku Chemicals. 2E4MZ Hardening accelerator, purchased from Sigma-Aldrich. NQ2035V SiO2 filler was purchased from Jiangsu NOVORAY New Material. Q099 The SiO2 filler was purchased from Suzhou GINET New Material. 2214 The SiO2 filler was purchased from Zhejiang Sanshi New Material Technology.

[0082] 3.3. Synthesis of Cyanate Esters

[0083] [Synthesis Example 1]

[0084] First, 100 grams of a cyanate monomer having the structure of formula (B-1) was dissolved in 30 grams of toluene to obtain a homogeneous solution. Next, the homogeneous solution was placed under a nitrogen atmosphere and stirred at 90°C to 110°C for 5 hours to carry out a polymerization reaction. Afterwards, the solvent was removed using a rotary thiocyanate concentrator to obtain a crude product. The crude product was then washed several times with methanol, and the solvent was removed again using a rotary thiocyanate concentrator to obtain cyanate resin 1. The Mn of cyanate resin 1 was measured according to the method described above, and the result was 1500 to 2500. [Formula (B-1)]

[0085] [Synthesis Example 2]

[0086] First, 100 grams of a cyanate monomer having the structure of formula (B-2) was dissolved in 30 grams of toluene to obtain a homogeneous solution. Next, the homogeneous solution was placed under a nitrogen atmosphere and stirred at 90°C to 110°C for 3 hours to carry out the polymerization reaction. Afterwards, the solvent was removed using a rotary thiocyanate concentrator to obtain a crude product. The crude product was then washed several times with methanol, and the solvent was removed again using a rotary thiocyanate concentrator to obtain cyanate resin 2. The Mn of cyanate resin 2 was measured according to the method described above, and the result was 1500 to 2500. [Formula (B-2)]

[0087] [Synthesis Example 3]

[0088] First, 100 grams of a cyanate monomer having the structure of formula (B-3) was dissolved in 30 grams of toluene to obtain a homogeneous solution. Next, the homogeneous solution was placed under a nitrogen atmosphere and stirred at 90°C to 110°C for 5 hours to carry out the polymerization reaction. Afterwards, the solvent was removed using a rotary thiocyanate concentrator to obtain a crude product. The crude product was then washed several times with methanol, and the solvent was removed again using a rotary thiocyanate concentrator to obtain cyanate resin 3. The Mn of cyanate resin 3 was measured according to the method described above, and the result was 2100 to 2800. [Formula (B-3)]

[0089] [Synthesis Example 4]

[0090] First, 100 grams of a cyanate monomer having the structure of formula (B-4) was dissolved in 30 grams of toluene to obtain a homogeneous solution. Next, the homogeneous solution was placed under a nitrogen atmosphere and stirred at 90°C to 110°C for 3 hours to carry out the polymerization reaction. Afterwards, the solvent was removed using a rotary thiocyanate concentrator to obtain a crude product. The crude product was then washed several times with methanol, and the solvent was removed again using a rotary thiocyanate concentrator to obtain cyanate resin 4. The Mn of cyanate resin 4 was measured according to the method described above, and the result was 2500 to 3000. [Formula (B-4)]

[0091] [Synthesis Example 5]

[0092] First, 100 grams of a cyanate monomer having the structure of formula (B-5) was dissolved in 30 grams of toluene to obtain a homogeneous solution. Next, the homogeneous solution was placed under a nitrogen atmosphere and stirred at 90°C to 110°C for 4 hours to carry out a polymerization reaction. Afterwards, the solvent was removed using a rotary thiocyanate concentrator to obtain a crude product. The crude product was then washed several times with methanol, and the solvent was removed again using a rotary thiocyanate concentrator to obtain cyanate resin 5. The Mn of cyanate resin 5 was measured according to the method described above, and the result was 1500 to 2800. [Formula (B-5)]

[0093] [Synthesis Example 6]

[0094] First, 100 grams of a cyanate monomer having the structure of formula (B-6) was dissolved in 30 grams of toluene to obtain a homogeneous solution. Next, the homogeneous solution was placed under a nitrogen atmosphere and stirred at 90°C to 110°C for 1 hour to carry out the polymerization reaction. Afterwards, the solvent was removed using a rotary thiocyanate concentrator to obtain a crude product. The crude product was then washed several times with methanol, and the solvent was removed again using a rotary thiocyanate concentrator to obtain cyanate resin 6. The Mn of cyanate resin 6 was measured according to the method described above, and the result was 500 to 900. [Formula (B-6)]

[0095] [Synthesis Example 7]

[0096] First, 100 grams of a cyanate monomer having the structure of formula (B-6) above was dissolved in 30 grams of toluene to obtain a homogeneous solution. Next, the homogeneous solution was placed under a nitrogen atmosphere and stirred at 90°C to 110°C for 2 hours to carry out the polymerization reaction. Afterwards, the solvent was removed using a rotary thiocyanate concentrator to obtain a crude product. The crude product was then washed several times with methanol, and the solvent was removed again using a rotary thiocyanate concentrator to obtain cyanate resin 7. The Mn of cyanate resin 7 was measured according to the method described above, and the result was 1100 to 1700.

[0097] 3.4. Preparation of Resin Composition

[0098] The resin compositions of Examples 1 to 9 and Comparative Examples 1 to 10 were prepared according to the proportions shown in Tables 2-1, 2-2, 2-3 and 2-4. The components were mixed at room temperature using a stirrer, and methyl ethyl ketone (purchased from Methyl Company) was added as a solvent. The resulting mixture was then stirred at room temperature for 60 to 120 minutes to obtain the respective resin compositions. In Tables 2-1, 2-2, 2-3 and 2-4, the weight parts of each component are based on the weight excluding the solvent.

[0099] Table 2-1: Composition of the resin compositions of Examples 1 to 5 weight Example 1 2 3 4 5 Bismaleimide resin (A) BMI-2300 45 80 20 BMI-70 45 MIR-3000-70MT 45 Cyanate ester resin (B) TA1000S 45 45 45 Cyanate resin 1 15 Cyanate ester resin 2 35 Benzoxazine compounds (C) JBZ-OP100N 10 5 15 JBZ-BF100N 10 JBZ-BA100N 10 hardening accelerator 2PI 0.01 0.01 0.01 0.01 0.01 filler NQ2035V 100 100 100 Q099 100 2214 100

[0100] Table 2-2: Composition of the resin compositions of Examples 6 to 9 weight Example 6 7 8 9 Bismaleimide resin (A) BMI-2300 35 45 45 45 Cyanate ester resin (B) Cyanate resin 3 50 Cyanate ester resin 4 45 Cyanate resin 5 45 Cyanate resin 7 45 Benzoxazine compounds (C) JBZ-OP100N 10 10 10 10 hardening accelerator 2PI 0.01 0.01 0.01 0.01 filler NQ2035V 100 100 300 100

[0101] Table 2-3: Composition of the resin compositions of Comparative Examples 1 to 5 weight Comparative example 1 2 3 4 5 Bismaleimide resin (A) BMI-2300 50 45 45 45 Cyanate ester resin (B) TA1000S 50 50 C01PS 45 CE01MO 45 C03CS 45 Benzoxazine compounds (C) JBZ-OP100N 20 10 10 10 hardening accelerator 2PI 0.01 0.01 0.01 0.01 0.01 filler NQ2035V 100 100 100 100 100

[0102] Table 2-4: Composition of the resin compositions of Comparative Examples 6 to 10 weight Comparative example 6 7 8 9 10 Bismaleimide resin (A) BMI-2300 45 45 45 45 45 Cyanate ester resin (B) C05CS 45 C06MO 45 C09MO 45 CE07MO 45 Cyanate resin 6 45 Benzoxazine compounds (C) JBZ-OP100N 10 10 10 10 10 hardening accelerator 2PI 0.01 0.01 0.01 0.01 0.01 filler NQ2035V 100 100 100 100 100

[0103] 3.5. Preparation and performance testing of prepreg and metal foil laminate

[0104] Prepregs and metal foil laminates were prepared using the resin compositions of Examples 1 to 9 and Comparative Examples 1 to 10, respectively. First, glass fiber cloth (model: 1078, thickness: 0.05 mm) was impregnated with the resin compositions of Examples 1 to 9 and Comparative Examples 1 to 10 using a roller coater, and the thickness of the glass fiber cloth was controlled to an appropriate level. Next, the impregnated glass fiber was placed in a dryer at 175°C and dried for 2 to 15 minutes to obtain a prepreg in a semi-cured state (stage B) (the resin content of the prepreg was about 52%). Then, several prepregs were laminated, and a 1 / 3 ounce copper foil was laminated on the outermost layer of each side, and then placed in a hot press for high-temperature hot pressing curing. The hot pressing conditions were as follows: the temperature was increased to 200°C to 220°C at a heating rate of 2.0°C / min to 3.0°C / min, and then hot-pressed at 200°C to 220°C for 180 minutes at a total pressure of 15 kg / cm² (initial pressure of 8 kg / cm²) to obtain the metal foil laminates of Examples 1 to 9 and Comparative Examples 1 to 10.

[0105] The properties of the metal foil laminates of Examples 1 to 9 and Comparative Examples 1 to 10, including Tg, upper limit of the number of holes and multilayer hot pressing heat resistance, were measured according to the measurement methods described above, and the results were recorded in Tables 3-1 and 3-2.

[0106] Table 3-1: Properties of the metal foil laminates of Examples 1 to 9 Tg Maximum number of holes Multilayer hot pressing heat resistance Example 1 269°C 6000 holes >60 times Example 2 267°C 6000 holes >60 times Example 3 261°C 7000 holes >60 times Example 4 273°C 7000 holes >60 times Example 5 255°C 8000 holes >60 times Example 6 263°C 7000 holes >60 times Example 7 261°C 7000 holes >60 times Example 8 265°C 7000 holes >60 times Example 9 268°C 5000 holes >60 times

[0107] Table 3-2: Properties of metal foil laminates in Comparative Examples 1 to 10 Tg Maximum number of holes Multilayer hot pressing heat resistance Comparative Example 1 180°C 5000 holes 2 times Comparative Example 2 230°C 6000 holes 5 times Comparative Example 3 259°C 3000 holes >60 times Comparative Example 4 266°C 2000 holes >60 times Comparative Example 5 260°C 3000 holes >60 times Comparative Example 6 269°C 2000 holes >60 times Comparative Example 7 264°C 3000 holes >60 times Comparative Example 8 264°C 3000 holes >60 times Comparative Example 9 264°C 3000 holes >60 times Comparative Example 10 268°C 4000 holes >60 times

[0108] As shown in Table 3-1, the results of Examples 1 to 9 demonstrate that the metal foil laminate prepared by the resin composition of the present invention can simultaneously possess high Tg, high upper limit of the number of drilled holes, and excellent multilayer hot pressing heat resistance (i.e., more than 60 repeated hot pressing cycles). Specifically, Examples 1 to 3 show that when the resin composition contains the same cyanate resin (B) (having a molecular weight within a specified range), even if the types of bismaleimide resin (A) and / or benzoxazine compound (C) are changed, the prepared metal foil laminate can simultaneously possess high Tg, high upper limit of the number of drilled holes, and excellent multilayer hot pressing heat resistance. Examples 1 and 7 to 9 show that when the resin composition contains the same bismaleimide resin (A) and benzoxazine compound (C), as long as the Mn of the cyanate resin (B) is within a specified range, the prepared metal foil laminate can simultaneously possess high Tg, high upper limit of the number of drilled holes, and excellent multilayer hot pressing heat resistance. Examples 4 to 6 further demonstrate that, even if the contents of bismaleimide resin (A), cyanate ester resin (B), and benzoxazine compound (C) in the resin composition are changed, as long as their contents are within the range specified in this invention, the resulting metal foil laminate can simultaneously possess high Tg, high upper limit of the number of drill holes, and excellent multilayer hot pressing heat resistance.

[0109] In contrast, as shown in Tables 3-2, the metal foil laminates prepared by resin compositions not of the present invention cannot simultaneously possess high Tg, a high upper limit for the number of drilled holes, and excellent multilayer hot-pressing heat resistance. Specifically, Comparative Examples 1 and 2 show that if the resin composition does not simultaneously contain bismaleimide resin (A), cyanate ester resin (B), and benzoxazine compound (C), the resulting metal foil laminate has a low Tg and poor multilayer hot-pressing heat resistance. Comparative Examples 3 to 10 show that if the cyanate ester resin contained in the resin composition does not have Mn within a specified range, the resulting metal foil laminate has a low upper limit for the number of drilled holes, which is detrimental to subsequent processing.

[0110] The above embodiments are merely illustrative of the principles and effects of the present invention and to illustrate the technical features of the present invention, and are not intended to limit the scope of protection of the present invention. Any changes or arrangements that can be easily made by those skilled in the art without departing from the technical principles of the present invention are within the scope claimed by the present invention. Therefore, the scope of protection of the present invention is as set forth in the appended claims.

Claims

1. A resin composition comprising: (A) a bismaleimide resin; (B) a cyanate ester resin having a number average molecular weight of 1,000 to 3,000; and (C) a benzoxazine compound, wherein, based on 100% by weight of the total weight of the solvent-free resin composition, the content of the bismaleimide resin (A) is 10% to 60% by weight, the content of the cyanate ester resin (B) is 7% to 35% by weight, and the content of the benzoxazine compound (C) is 1% to 15% by weight.

2. The resin composition as claimed in claim 1, wherein the bismaleimide resin (A) has a structure represented by formula (I): [Formula (I)], in which R4 is selected from the group consisting of methylene (-CH2-), 4,4'-diphenylmethane (), m-phenylene (), bisphenol A diphenyl etheryl (), 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane (), 4-methyl-1,3-phenylene (), (2,2,4-trimethyl)-1,6-hexyl (), and, wherein k is an integer from 0 to 5.

3. The resin composition as claimed in claim 1, wherein the bismaleimide resin (A) is selected from the group consisting of: 1,2-bismaleiminoethane, 1,6-bismaleiminohexane, 1,3-bismaleiminobenzene, 1,4-bismaleiminobenzene, 2,4-bismaleiminotoluene, 4,4'-bismaleiminodiphenylmethane, 4,4'-bismaleiminodiphenyl ether, 3,3'-bismaleiminodiphenyl ether, etc. -Dimaleiminodiphenyl sulfonate, 4,4'-Dimaleiminodiphenyl sulfonate, 4,4'-Dimaleiminodicyclohexylmethane, 3,5-bis(4-maleiminophenyl)pyridine, 2,6-bismaleiminopyridine, 1,3-bis(maleiminomethyl)cyclohexane, 1,3-bis(maleiminomethyl)benzene, 1,1-bis(4-maleiminophenyl)cyclohexane, 1,3-bis( Dichloromaleimino)benzene, 4,4'-biscitraconimidodiphenylmethane, 2,2-bis(4-maleiminophenyl)propane, 1-phenyl-1,1-bis(4-maleiminophenyl)ethane, α,α-bis(4-maleiminophenyl)toluene, 3,5-bismaleimino-1, 2,4-triazole, N,N'-epenylethyl bismaleimide, N,N'-hexamethylene bismaleimide, N,N'-m-epenylphenyl bismaleimide, N,N'-p-epenylphenyl bismaleimide, N,N'-α,α'-4,4'-dimethylenecyclohexane bismaleimide, N,N'-m-xylene bismaleimide, N,N'-4,4'-diphenylcyclohexane bismaleimide, and combinations thereof, wherein y is an integer from 1 to 4.

4. The resin composition as claimed in claim 1, wherein the cyanate resin (B) is selected from the group consisting of: 2,2-bis(4-cyanoxyphenyl)propane, 4,4'-ethylidene bis(phenyl)cyanate (4,4'-ethylidene) Bisphenylenecyanate, 4,4'-dicyanoxybiphenyl, bis(4-cyanoxy-3,5-dimethylbenzene)methane, bis(4-cyanoxyphenyl)sulfide, bis(4-cyanoxyphenyl) ether, prepolymers of bisphenol A dicyanate, 1,1-bis(4-cyanoxyphenyl)ethane, 1,1-bis(4-cyanoxyphenyl)methane, 1,3-bis(4-cyanoxyphenyl-1-(methylethylidene))benzene, bis(4-cyanoxyphenyl) ether, bis(4-cyanoxyphenyl)-2,2-butane, 1,3-bis[2-(4-cyanoxyphenyl)propyl]benzene, bis(4-cyanoxyphenyl)ethane, cyano-modified phenolic aldehydes, cyano-modified phenolic dicyclopentadiene adducts, and combinations thereof.

5. The resin composition as described in any one of claims 1 to 4 further comprises a curing accelerator selected from the group consisting of imidazole compounds, pyridine compounds, and combinations thereof.

6. The resin composition as claimed in any one of claims 1 to 4 further comprises a curing agent selected from the group consisting of: styrene, α-methylstyrene, ethylstyrene, propylstyrene, butylstyrene, triallyl isocyanurate (TAIC), triallyl cyanurate (TAC), 1,3-divinylbenzene, 1,4-divinylbenzene, 1,2-bis(p-vinylphenyl)ethane, 1,2-bis(m-vinylphenyl)ethane, 1-(p-vinylphenyl)-2-(m-vinylphenyl)ethane, and combinations thereof.

7. The resin composition as described in any one of claims 1 to 4 further comprises fillers selected from the group consisting of: silicon dioxide, aluminum oxide, magnesium oxide, magnesium hydroxide, calcium carbonate, talc, clay, aluminum nitride, boron nitride, aluminum hydroxide, aluminum silicon carbide, silicon carbide, sodium carbonate, titanium dioxide, zinc oxide, zirconium oxide, quartz, diamond, diamond-like material, graphite, calcined kaolin, baiji, mica, hydrotalcite, hollow silicon dioxide, polytetrafluoroethylene (PTFE) powder, glass beads, ceramic whiskers, carbon nanotubes, nano-sized inorganic powders, and combinations thereof.

8. A prepreg, which is prepared by impregnating or coating a substrate with a resin composition as described in any one of claims 1 to 7 and drying the impregnated or coated substrate.

9. A metal foil laminate, which is prepared by laminating a prepreg as described in claim 8 with a metal foil, or by directly coating a resin composition as described in any one of claims 1 to 7 onto a metal foil and drying the metal foil.

10. A printed circuit board made of a metal foil laminate as described in claim 9.